Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1186/1471-2334-12-293
|View full text |Cite
|
Sign up to set email alerts
|

Impact of gender on response to highly active antiretroviral therapy in HIV-1 infected patients: a nationwide population-based cohort study

Abstract: BackgroundImpact of gender on time to initiation, response to and risk of modification of highly active antiretroviral therapy (HAART) in HIV-1 infected individuals is still controversial.MethodsFrom a nationwide cohort of Danish HIV infected individuals we identified all heterosexually infected women (N=587) and heterosexually infected men (N=583) with no record of Hepatitis C infection diagnosed with HIV after 1 January 1997. Among these subjects, 473 women (81%) and 435 men (75%) initiated HAART from 1 Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 46 publications
(79 reference statements)
2
14
1
Order By: Relevance
“…The immunological advantage women had over men during AHI strengthened over the first year of ART and was then maintained with sustained ART. Some studies have reported that women have greater CD4 + gain than men one to three years after initiating ART [31,37‐41], whereas in others, CD4 + T‐cell counts rose similarly between men and women [29,42‐45]. Here we observed that women retained a higher CD4 + T‐cell count than men throughout follow‐up under ART.…”
Section: Discussionsupporting
confidence: 53%
“…The immunological advantage women had over men during AHI strengthened over the first year of ART and was then maintained with sustained ART. Some studies have reported that women have greater CD4 + gain than men one to three years after initiating ART [31,37‐41], whereas in others, CD4 + T‐cell counts rose similarly between men and women [29,42‐45]. Here we observed that women retained a higher CD4 + T‐cell count than men throughout follow‐up under ART.…”
Section: Discussionsupporting
confidence: 53%
“…Similarly to other cohorts , women starting cART were younger, were more frequently of non‐white ethnicity, were less educated, and had higher CD4 cell counts and lower HIV RNA than men. In line with the findings of other studies , after adjustment for potential confounders, no major differences in virological suppression at 1, 2 and 5 years were observed between the sexes in a setting of equal access to cART. In multivariate analysis, among sociodemographic factors, only non‐white ethnicity was an independent risk factor for not achieving virological suppression, suggesting that immigration (mainly from sub‐Saharan Africa to Switzerland) may explain differences in virological suppression between the sexes.…”
Section: Discussionmentioning
confidence: 75%
“…This observation is supported by higher CD4 cell counts in women than men among HIV‐negative patients, and higher immune activation in the presence of HIV infection . By contrast, several reports indicated similar increases in CD4 cell counts between the sexes . However, discrepancies among these studies may be explained by differences in the study populations, with some studies including patients with different lifestyles such as MSM , and lower proportions of women precluding the detection of such small differences.…”
Section: Discussionmentioning
confidence: 96%
“…[14][15][16] Sex may also modify the response to ART among HIV-infected individuals. While some studies have found no association of sex with response to ART, [17][18][19] others have suggested that women have superior virologic, immunologic, and clinical outcomes compared with men. [20][21][22][23][24] It is unknown if this is attributable to biological factors, such as pharmacokinetics, 25,26 or behavioral or structural factors, such as adherence 27 or access to or quality of care.…”
Section: Introductionmentioning
confidence: 95%